The development of an agricultural incomes policy - Attwood, E. A. (Statistical and Social Inquiry Society of Ireland, 1970)
Considerable attention is now being given in Ireland to the development of an incomes policy for the community. There is general agreement that such a policy should apply to all incomes?not only to wages and salaries but also to dividends, rents, professional earnings and to earnings from self-employment. In the self-employed category, by far the most important group is that of farmers and their families. At present there are 270,000 farm family members engaged in agriculture (plus 36,000 hired workers) and the application of an incomes policy to their incomes is as important as it is to the other income groups.
Read before the Society, 20 February 1970
Keywords: Irish agriculture; Incomes policy; Income distribution; Agricultural incomes policy; 314.15